Comparing the Main Anthropometric and Biomechanical Indexes in Male Adult Wushu Athletes in Taolu and Sanda Disciplines - azam daneshvar; Heydar Sadeghi (Biyumikānīk-i varzishī, 2016)
Objective: The main aim of the study was comparing the main anthropometric and biomechanics indexes in elite male adult Wushu athletes in both Taolu and Sanda disciplines.